2009
DOI: 10.1097/aap.0b013e31819a27bd
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Procaine Is Less Neurotoxic Than Mepivacaine, Prilocaine and Bupivacaine in Rats

Abstract: In this animal model, the neurotoxicity of intrathecal procaine was the mildest, and the recovery time to ambulation with procaine was the fastest among the 4 tested anesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…As described in previous studies, 0.5% bupivacaine did not induce apoptosis in rat cortical astrocytes and has no neurotoxic damage [32,33]. And in the 0.5% bupivacaine 15-20 μl/h of TEA model, cardiorespiratory depression or extensive motor blockade were not observed in adult rats [7,34].…”
Section: Discussionmentioning
confidence: 80%
“…As described in previous studies, 0.5% bupivacaine did not induce apoptosis in rat cortical astrocytes and has no neurotoxic damage [32,33]. And in the 0.5% bupivacaine 15-20 μl/h of TEA model, cardiorespiratory depression or extensive motor blockade were not observed in adult rats [7,34].…”
Section: Discussionmentioning
confidence: 80%
“…The literature contains many clinical and laboratory reports concerning the neurotoxic effects of different LAs that were evaluated by neurite outgrowth, apoptosis, and clinical and histopathological changes (Johnson et al 2004, Kamiya et al 2005, Kasaba et al 2003, Kishimoto et al 2002, Lee et al 2009, Saito et al 2001, Sekimoto et al 2006, Takenami et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…bupivacaine for the central nervous and cardiovascular systems in animals 4,5 and humans. [6][7][8] In a series of studies, we determined the neurotoxicities of lidocaine, tetracaine, bupivacaine, mepivacaine, prilocaine, and procaine [9][10][11][12] in a rat spinal model. These studies showed that all these agents, with the exception of procaine, were neurotoxic, with lesions displaying common features irrespective of the anesthetic agent and affecting mainly axons of the dorsal root entry zone.…”
Section: Résumémentioning
confidence: 99%
“…Procaine was not neurotoxic even at ten times (20%) the clinical concentration. 12 We consider it important to base the ranking of local anesthetic toxicity on the severity and location of damage because: 1) laboratory information may be useful in predicting which local anesthetics can be employed safely in the clinical setting with minimal side effects; and 2) identifying the lesions that are typical of local anesthetic toxicity could help to determine neurological signs of toxicity and the differential diagnosis between anestheticinduced toxicity and other causes of postoperative neuropathy. The present work is an extension of our previous studies.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation